Correlation between Sleep Disorders and Function in Children with Spastic Cerebral Palsy - GHORBANPOUR, Zahra (Iran J Child Neurol, 2019)
OBJECTIVES: The aim of the present study was to explain the correlation between sleep disorders and function in children with spastic cerebral palsy (4-12 year). MATERIALS & METHODS: This cross-sectional study was carried out on 62 children with spastic CP (8.98±1.46 yr) recruited from rehabilitation clinics of Tehran, Iran in 2017. The Activities Scale for Kids, The Sleep Disturbance Scale for Children and the cerebral palsy Quality of Life questionnaire for Children were utilized in this study. Data were analyzed using SPSS software. RESULTS: Children with sleep disorder and arousal disorders had lower family health, lower quality of life and lower level of independence in their activities (P< 0.05). CONCLUSION: These results emphasize on the necessity of more attention about sleep disorders and family health problems in children with cerebral palsy.